Personal Finance Determinants Factors (Case Study on Management Master Students of Universitas Negeri Jakarta) - Deisy Siska Abriani; Gatot Nazir Ahmad; Unggul Purwohedi (LPPM Universitas Negeri Jakarta, 2020)
The objectives of this study are 1) to analyze the factors that influence personal financial behavior, 2) to test the hypothesis of the influence of financial knowledge, financial attitudes, locus of control, and income on personal financial behavior in Masters of Management students at the State University of Jakarta. The unit of analysis is students of Master of Management, State University of Jakarta. The observation unit was 110 respondents who were students of the Jakarta State University Management Masters who were registered from February 2015 to February 2017 with an active status and had received a matriculation program. Data collection techniques using questionnaires and observations. The data analysis technique used is Multiple Regression Analysis and Univariate One-Way ANOVA Test with SPSS 22. The results of the descriptive analysis showed: a) The level of financial knowledge of the respondents reached 83%; b) Financial Attitude has the highest index compared to other dimensions (87%), and c) Locus of Control (79%). The hypothesis testing results show 1) There is an effect of financial knowledge on financial behavior with the tstatistic obtained by 3,968> ttable = 1,659 and prob. value = 0,000 <0.05, then H1 is accepted and significant. 2) There is a direct and significant positive effect of financial attitudes on personal financial behavior with the tstatistic obtained at 4,700> ttable = 1.659 and the value of prob. value = 0.000 <0.05, then H1 is accepted and significant. 3) Locus of control has not influenced personal financial behavior with the t-statistic obtained is 0.257 <ttable = 1.659 and the value of prob.value = 0.798> 0.05, then H1 is not accepted. 4) Income has a significant influence on personal financial behavior, with the test results showing an F value of 3,436 with a Sig of 0.020 <0.05, so H1 is acceptable, so it can be concluded that there is a significant difference in the personal financial behavior of respondents based on the four income categories. Testing the hypothesis proves that income affects personal financial behavior.